Financing capacity investment under demand uncertainty - Francis de Véricourt; Denis Gromb (European School of Management and Technology (ESMT), 2014)
This paper studies the interplay between the operational and financial facets of capacity investment. We consider the capacity choice problem of a firm with limited liquidity and whose access to external capital markets is hampered by moral hazard. The firm must therefore not only calibrate its capacity investment and the corresponding funding needs, but also optimize its sourcing of funds. Importantly, the set of available sources of funds is derived endogenously and includes standard financial claims (debt, equity, etc.). We find that when higher demand realizations are more indicative of high effort, debt financing is optimal for any given capacity level. In this case, the optimal capacity is never below the efficient capacity level but sometimes strictly above that level. Further, the optimal capacity level increases with the moral hazard problem's severity and decreases with the firm's internal funds. This runs counter to the newsvendor logic and to the common intuition that by raising the cost of external capital and hence the unit capacity cost, financial market frictions should lower the optimal capacity level. We trace the value of increasing capacity beyond the efficient level to a bonus effect and a demand elicitation effect. Both stem from the risk of unmet demand, which is characteristic of capacity decisions under uncertainty.
urn:nbn:de:101:1-201405275859
Keywords: 650; Capacity; optimal contracts; financial constraints; newsvendor model